Investigating the association between discrimination, internalizing symptoms, and alcohol use among Latino/a immigrants in the United States - Macias Burgos, Miracle A.; Bautista, Tara G.; Cruz-Carrillo, Yesenia; Cisco, Mia; Sahbaz, Sumeyra; Nehme, Lea; Vo, Duyen; Duque, Maria; Schwartz, Seth J.; Montero-Zamora, Pablo (Frontiers in Psychiatry, 2024)
Internalizing symptoms associated with anxiety and depression are correlated with harmful alcohol use, but little is known about the association between perceived discrimination and harmful alcohol use. The present study was designed to investigate the association between perceived discrimination, internalizing symptoms associated with anxiety and depression, and harmful alcohol use among Latino/a immigrants living in the United States. Our sample included 426 Latino/a immigrants, mean age was 40.05 years (SD = 6.50), 65.50% were women, 80.00% had a partner, 54.20% lived on less than 2,000 a month, and 41.50% had a college degree. Perceived discrimination was assessed using the Perceived Discrimination Scale, anxious symptoms were assessed using the GAD-7, depressive symptoms were assessed using the CES-D SF, and harmful alcohol use was assessed using AUDIT. The linear regression model was statistically significant, R 2 = 0.38, F (8, 425) = 32.09, p < 0.01. Discrimination was significantly associated with AUDIT scores, (β = 0.21, p < 0.01) after accounting for covariates and for symptoms of anxiety and depression. Our results indicate that experiences of discrimination in the US are associated with increased harmful alcohol use even after controlling for other variables. These findings may be useful in designing coping interventions specifically for Latino/a immigrants to reduce the risk of alcohol use disorder. This study also has political and public health implications for acknowledging the detrimental health consequences of experiencing discrimination, providing support to the position that reducing racism and discrimination represent important public health priorities.